COMPARISON OF URINE GLUCOSE LEVELS IN DIABETES MELITUS TYPE 2 USING REDUCTION AND OPTICAL DENSITY METHODS IN HOSPITAL. PROF. DR. ALOEI SABOE - Noveling Jovancha Pongoh (Journal of Health, Technology and Science (JHTS), 2020)
Diabetes Mellitus (DM) is a chronic disease that is characterized by blood glucose levels that exceed normal caused by the malfunctioning of the pancreas in producing sufficient insulin (DM type 1) or the body's inability to use insulin that has been produced (DM type 2). When glucose in the blood increases, the sugar will be excreted in urine, this is called glucosuria. Urine glucose testing is a chemical examination and as a screening test for diabetics. Urine glucose testing can be done by several methods including the reduction method and optical density method. The purpose of this study was to determine the comparison of urine glucose levels in patients with type 2 diabetes mellitus using the re-duction method and optical density method in hospitals. Prof. Dr. Aloei Saboe. This research is a quantitative study with a pre-experimental design. The sampling technique was purposive sampling that is by setting specific criteria in inclusion and exclusion. 2-hour PP (Postprandial) urine samples from inpatients with type 2 of diabetes mellitus. Each urine sample was tested by two methods, namely the reduction method using Reagent benedict and the optical density method using a urine analyzer. Glucosuria levels of both types of examinations are interpreted semiquantitatively. Then compare the results of the two methods. Data were analyzed by paired sample t-test using SPSS (Statistical Packege for Social Science). Paired sample t-Test statistical test showed a significant value of 0,000 with a significance level of 0.05, 0.000 <0.05. So it can be concluded that there are differences in the urine glucose levels of patients with type 2 diabetes using the reduction method and optical density method